Imaging of Foreign Bodies - Pinto, Antonio; Romano, Luigia (Springer Milan : Imprint: Springer, 2014)
Most ingested foreign bodies pass through the gastrointestinal tract without a problem. However, both ingested and inserted foreign bodies may cause serious complications, such as bowel obstruction or perforation. Foreign body aspiration is common in children, especially those under 3 years of age, and in these cases chest radiography and CT are the main imaging modalities. This textbook provides a thorough overview of the critical role of diagnostic imaging in the assessment of patients with suspected foreign body ingestion, aspiration, or insertion. A wide range of scenarios are covered, from the common problem of foreign body ingestion or aspiration in children and mentally handicapped adults through to drug smuggling by body packing and gunshot wounds. Guidance is offered on diagnostic protocols, and the value of different imaging modalities in different situations is explained. Helpful management tips are also provided. This textbook will prove invaluable for residents in radiology, radiologists, and physicians who are involved on a daily basis, within an emergency department, in the management of patients with suspected ingestion, aspiration, or insertion of foreign bodies.  .